Does plasma oxytocin mediate stress reduction after compassion-based mental training?. (September 2021) - Hoehne, Katja; Vrticka, Pascal; Engert, Veronika; Singer, Tania
Abstract : Based on its role in social processing and stress, oxytocin was suggested to mediate stress reduction after compassion-based mental training. In the ReSource Project, a 9-month longitudinal mental training study, we first examined oxytocin's role in psychosocial stress reduction after training socio-affective (i.e., compassion-based, Affect Module), socio-cognitive or attentional skills (Perspective and Presence Modules, n=313). In a second study, using a subsample (n=113), we explored the effect of one compassion (Loving-kindness) meditation (LKM) on oxytocin, cortisol and subjective responses after 3-month Affect training (vs. rest with no training). Independent of training, stress triggered acute oxytocin release (p<0.001). LKM did not elicit acute oxytocin responses. Training effects were found in overall oxytocin levels in both studies. Compared to no training, Affect training decreased overall oxytocin during stress (p<0.05, d=0.50) but increased it during LKM (p<0.001, d=-0.72). Overall oxytocin changes were unrelated to cortisol and subjective stress reactivity. Based on Quintana and Guastella's (2020) theory of oxytocin as an allostatic hormone with anticipatory features, we interpret training-induced oxytocin changes as shifts in the anticipated emotional relevance of events. After 3-month Affect training, stress may have lost its emotional saliency, while LKM gained in emotional relevance. Finally, oxytocin does not mediate stress reduction after mental training.